2004
DOI: 10.1093/ajcn/79.4.646
|View full text |Cite
|
Sign up to set email alerts
|

Changes in maternal weight from the first to second trimester of pregnancy are associated with fetal growth and infant length at birth

Abstract: Background: Despite our knowledge of the negative consequences of stunting during early childhood and the important role that maternal nutritional status plays in the development of intrauterine growth retardation, we do not know the extent to which maternal nutritional status influences the growth in length of the fetus or whether a sensitive period for fetal linear growth exists during gestation. Objective: Our objective was to explore the relation between maternal weight gain during different stages of preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 28 publications
6
53
0
1
Order By: Relevance
“…One assessed only linear intrauterine growth and found that second to third trimester weight gain was associated with increased femur and tibia length. [8] We observed that FL was most impacted by maternal weight gain early in pregnancy. Another study found that overall maternal weight gain was associated with increases in AC and abdominal lean mass, but no other fetal biometrics such as FL or BPD.…”
Section: Commentmentioning
confidence: 97%
See 1 more Smart Citation
“…One assessed only linear intrauterine growth and found that second to third trimester weight gain was associated with increased femur and tibia length. [8] We observed that FL was most impacted by maternal weight gain early in pregnancy. Another study found that overall maternal weight gain was associated with increases in AC and abdominal lean mass, but no other fetal biometrics such as FL or BPD.…”
Section: Commentmentioning
confidence: 97%
“…Also, most prior research related to fetal growth was limited to total weight gain,[3] which limits detection of critical periods where maternal weight may be more or less important for fetal growth, [46] and has methodological limitations. [7] Previous longitudinal gestational weight gain and intrauterine fetal growth studies have been limited by small sample sizes,[8, 9] did not examine the changing dynamics between weight gain and fetal growth across gestation,[9] or only examined longitudinal linear growth. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Lastly, our study sample comprised largely of non-Hispanic white mothers with at least a high school education. Only few previous studies were conducted among racially/ethnically or low socio-economic status women(9, 26). These studies generally reported measures that were not comparable to ours or findings that were similar.…”
Section: Commentsmentioning
confidence: 99%
“…Stunted newborns have worse prospects of later life-quality, a risk of stunting in childhood and adult age, cognitive problems and school performance, and physical work capacity. Notwithstanding these potential deficiencies, they have higher chances of perinatal survival: 'when developing in a nutritionally poor environment, those foetuses that will survive best are those who can adapt, by being smaller or having a slower metabolic rate' (Kunz and King 2007, p. 72; see also Hack et al 1995;Yaqub 2002;Neufeld et al 2004). In contrast, wasted IUGR infants exhibit greater postnatal catch-up growth and less severe cognitive defects than stunted infants, but also higher rates of neonatal morbidity and neonatal and perinatal mortality, as well as a predisposition to later morbidity (Kramer 1987;Villar et al 1990;Caulfield et al 1991;Norton 1994;Henriksen 1997;Kunz and King 2007).…”
Section: Temporary Maternal Malnutritionmentioning
confidence: 99%
“…There are three main phases in which maternal nutrition may affect the health of the child: in early pregnancy, influencing the development of the embryo or placentation; slightly later during organogenesis, altering the number and functions of cell types; and in late gestation after fetal organs have been formed, affecting the regulatory set points by which they function (Kunz and King 2007;Mullis and Tonella 2008). Birth weight and fetal linear growth are strictly related both to maternal nutritional status at the beginning of gestation and to the rate of maternal fat deposition from the first to the second trimester of pregnancy (Villar et al 1992;Norton 1994;Li et al 1998;Neufeld et al 2004;Kind et al 2006). In early pregnancy, absolute nutrient requirements for fetal growth are small but fetal metabolic activity and specific growth rate are high.…”
Section: Temporary Maternal Malnutritionmentioning
confidence: 99%